Peculiarities of the higher education development in a blended learning environment - Pavlo Chervonyi; Svitlana Alieksieieva; Nadiia Senchylo-Tatlilioglu; Oleksandr Chastnyk; Nataliia Diomidova (Revista on line de Política e Gestão Educacional)
This article aims to identify the peculiarities of the higher education pedagogy transformation through the blended learning model. The methodology was based on a statistical, correlational analysis by using The Teaching and Learning International Survey database containing the survey results of 7,823 educators in France and the Netherlands. The study revealed an average level of teacher preparation for blended learning (50.5%) and preparation for information and communication technology (ICT) use in student learning (48.4%) components inclusion. A significant level of teachers’ professional development of ICT skills was revealed (44% take courses). An average level of teachers’ unpreparedness both for blended learning (28.9% not ready, 36.6% not prepared enough) and ICT use in practice was established (30.3% almost not ready, 34.25 not prepared enough). A positive correlation was established between the teachers’ preparation for the blended learning environment and the passage of professional ICT skills development courses.